Prosocial Leadership Understanding the Development of Prosocial Behavior within Leaders and their Organizational Settings - Ewest, Timothy (Palgrave Macmillan US, 2018)
This book explores the behavioral phenomenon that is intended to aid in the benefit of others, known as prosocial behavior. The author combines eight years of quantitative and qualitative research to explain and delineate the antecedents to prosocial leadership and align these findings into an understandable model for prosocial leadership development. This ground-breaking text is the first to combine the elements of prosocial followership, development and altruism as essential components to leadership. It further explores the behaviors, values and ideas leading to the formation of prosocial leadership within individuals and organizations.